Influencer - "Patterson, Kerry, 1946-" (New York)
Includes bibliographical references and index. You're an influencer -- Find vital behaviors -- Change the way you change minds -- Make the undesirable desirable : personal motivation -- Surpass your limits : personal ability -- Harness peer pressure : social motivation -- Find strength in numbers : social ability -- Design rewards and demand accountability : structural motivation -- Change the environment : structural ability -- Become an influencer.
Keywords: INFLUENCE (PSYCHOLOGY);LEADERSHIP.;POWER (PSYCHOLOGY).;SOCIAL BEHAVIOR.;PSYCHOLOGY -- POPULAR WORKS